On further properties of minimal size in hypergroups of type U on the right. Issue 10 (2nd October 2020) - Heidari, Dariush; Freni, Domenico
Abstract: In this paper, we prove that the minimum size of a hypergroup of type U on the right which contains a proper subsemihypergroup of type U on the right of size 6 and a subgroup of size ≥ 2 is 18. We study some properties of hypergroups of type U on the right of size 2 p that have a cyclic subgroup of size p . Moreover, we give a more general answer to a problem left open in [11 ].